Melacak Akar Permasalahan Hubungan Antara Sunni dan Syi’ah - Abdullah AF; Syamzan Syakur; Susmihara (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The classic slander in the growth and development of Islam from time to time is the Shi'a problem which is a separate group outside the Muslim groups in general which is called ahlussunnah or sunni. So that disputes between Shia and Sunni do not only occur in the Gulf States or Arab countries, but Sunni and Shia disputes extend to Islamic countries in various parts of the world, including Indonesia. At first the Shiites were a cultural group who empathized with Ali bin Ali Talib and named themselves Shi'ah 'Ali (supporters of 'Ali), where they saw that Ali bin Abi Talib had more rights to become a leader after the death of the Prophet Muhammad than his companions. another. However, in its journey this group which was originally cultural in nature then transformed into a group with a political and Aqidah pattern to this day. The difference between the Shia and the Sunni is not only the difference in the schools of law, but the Shia differs from Muslims in general in very basic matters, including the pillars of Islam and the pillars of faith, in the theology of the Imamate where the Shia only believe in the Imams. their imam as a leader, on the issue of taqiyah where the Shi'a equate taqiyah with prayer services, while in ahlussunnah wal jama'ah it is not known as taqiyah, respecting the companions of the Prophet in such a way, but not so in the yi'ah understanding. The Shi'a judged the Prophet's companions negatively to a very extreme level.